87Sr/86Sr and trace element mapping of geosphere-hydrosphere-biosphere interactions: A case study in Ireland. (May 2018) - Ryan, Saskia E.; Snoeck, Christophe; Crowley, Quentin G.; Babechuk, Michael G.
Abstract: Geochemical mapping of biosphere variation has wide application to geological, environmental, forensic and archaeological research. The extent to which trace elements may be used to complement strontium isotopes ( 87 Sr/ 86 Sr) for biosphere characterisation is unclear and uncertainties exist regarding the most suitable sample media for this purpose. Here, the variation in 87 Sr/ 86 Sr and trace elements, with focus on the rare earth elements and yttrium (REE + Y), are measured in soil leachates, vegetation and streamwaters. These independent tracers are employed to define geochemical reservoirs and quantify soil-plant-water interactions in a geologically diverse and archaeologically significant area of Ireland, County (Co.) Meath. This integrated isotope and element approach produces the first combined dataset for this temperate environment. Biological absorption coefficients (BAC) are used to assess bio-uptake of selected elements. The REE + Y exhibited greatest utility in revealing soil parameter controls on bio-uptake, such as reduced availability from preferential retention of Ce on Fe/Mn-oxyhydroxide surfaces, as well as revealing a preferential uptake of Y relative to HREE. High Y/Ho ratios (65.3–465) are exhibited in ash trees ( Fraxinus excelsior L.), regardless of geological setting, indicating a potential species-specific preference. However, aerial portions of ash trees do not directly reflect the REE in the bioavailable portion of the soil, indicating selectivity from the soil reservoir or fractionation during plant uptake and/or intra-plant distribution. Streamwater REE patterns have a consistent and seawater-like pattern probably inherited from marine carbonate bedrock, surficial marine carbonate-derived till, agricultural fertiliser or a combination of all three, and thus were not site lithology diagnostic. By contrast, distinct variation in sources of 87 Sr/ 86 Sr to streamwaters is evident and reflects small-scale differences in underlying bedrock. The 87 Sr/ 86 Sr range of vegetation for the study area is 0.7081–0.7130. Soil and streamwater samples collected at proximal locations to the vegetation demonstrated a range of 0.7086–0.7133 for soil leachates and 0.7081 to 0.7107 for streamwaters. Statistically significant (p < .05) differences between the spatial distribution of 87 Sr/ 86 Sr in plants and certain underlying bedrock/Quaternary sediment were identified, even in a region without an extreme range in 87 Sr/ 86 Sr values. Careful selection of appropriate soil leaching protocols is necessary for an informative estimate of the natural ranges that exist within the pedosphere, supporting the notion that plant material is the most suitable sample medium for mapping bioavailable Sr. The high degree of spatial variability in 87 Sr/ 86 Sr and differences between reservoirs can only be accurately represented by relatively high-density sampling of plants. These data complement both national and European-wide initiatives to produce large-scale 87 Sr/ 86 Sr biosphere maps. Highlights: 87 Sr/ 86 Sr and trace elements (namely REE+Y) were determined in streamwater, soil leaches and plants. Biological absorption coefficients reveal preferential uptake of Y over REE in ash trees. REE+Y of streamwater resemble those of seawater, indicating interaction with carbonates. Significant (p<0.05) correlations exist between 87 Sr/ 86 Sr in plants and underlying bedrock/sediment. Plants are the most suitable medium for constraining bioavailable 87 Sr/ 86 Sr.